The effect of preseason training on mucosal immunity in male basketball players - Azarbayjani, M. A.; Nikbakht, H.; Rasaee, M. J. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: This study examined the effects of pre season training on restring level and acute response of mucosal immunity in male basketball players. METHODS: Twenty male basketball players performed 8 weeks progressive exercise training, consisting of interval and continuous parts. Five mL unstimulated saliva was collected from each subject before, immediately and one hour after the end of one bout of exercise to exhaustion on treadmill at the beginning of the first week and end of 8 weeks to determine the acute responses. At the beginning of each 2 weeks (resting state) induced changes in basal mucosal immunity was evaluated. The concentration of sIgA and total protein was measured by the ELISA and Bradford methods respectively. RESULTS: One bout exercise training at beginning of first week decreased significantly sIgA level but not at the end of 8th week. Total protein did not change significantly at 1st week after exercise, but at eight week significantly increased and remained at high level until one hour after exercise. sIgA to total protein ratio at first week significantly decreased and remained constant one hour after exercise. At the eight week sIgA decreased significantly immediately after exercise and remained low until one hour after exercise. The comparison of sIgA and total protein levels indicates significant decrease after eight weeks training. CONCLUSION:These results suggest that repetition of single bout of exercise training have a cumulative effect on the mucosal immune system.